Design and Synthesis of Non-Covalent Imidazo[1,2-a]quinoxaline-Based Inhibitors of EGFR and Their Anti-Cancer Assessment - Manvendra Kumar; Gaurav Joshi; Sahil Arora; Tashvinder Singh; Sajal Biswas; Nisha Sharma; Zahid Rafiq Bhat; Kulbhushan Tikoo; Sandeep Singh; Raj Kumar (Molecules, 2021)
A series of 30 non-covalent imidazo[1,2-a]quinoxaline-based inhibitors of epidermal growth factor receptor (EGFR) were designed and synthesized. EGFR inhibitory assessment (against wild type) data of compounds revealed 6b, 7h, 7j, 9a and 9c as potent EGFRWT inhibitors with IC50 values of 211.22, 222.21, 193.18, 223.32 and 221.53 nM, respectively, which were comparable to erlotinib (221.03 nM), a positive control. Furthermore, compounds exhibited excellent antiproliferative activity when tested against cancer cell lines harboring EGFRWT; A549, a non-small cell lung cancer (NSCLC), HCT-116 (colon), MDA-MB-231 (breast) and gefitinib-resistant NSCLC cell line H1975 harboring EGFRL858R/T790M. In particular, compound 6b demonstrated significant inhibitory potential against gefitinib-resistant H1975 cells (IC50 = 3.65 μM) as compared to gefitinib (IC50 > 20 μM). Moreover, molecular docking disclosed the binding mode of the 6b to the domain of EGFR (wild type and mutant type), indicating the basis of inhibition. Furthermore, its effects on redox modulation, mitochondrial membrane potential, cell cycle analysis and cell death mode in A549 lung cancer cells were also reported.